SPORTS BY CHOICE OR BY SOCIO-ECONOMIC STATUS - Singh Rattan, Dr. Jaswinder (The journal of contemporary issues in business and government, 2019)
The aim of the present study is to examine the effect of socio-economic status on sports performance of wrestling players of Haryana State. A sample of 100 Wrestles is selected for the investigation. Socio-economic status of players was measured with the use of the socio-economic status scale prepared by R.L Bharadwaj (1983). The sports performance scale was prepared by researcher herself according to player’s highest achievement in competition at different levels. Findings of the study show that there is a positive significant effect of socio economic status on sports performance of wrestlers of Haryana State.